Metodologi Pemahaman Hadis M. Yusuf al-Qaradhawi: Studi Analitis Atas Hadis Partisipasi Wanita Dalam Berpolitik - Choiroh, Wahyuni Nuryatul; Munawir, Munawir (UIN Sultan Syarif Kasim Riau, 2023)
Sunni scholars view Hadith as a normative source capable of embodying the essence of the Qur'an, considering Hadith's position as the second source of Islamic religious teachings after the Qur'an. The controversy between textual and contextual schools of thought regarding the study of Hadith has existed since the early development of Islam. Even to this day, textualist scholars continue to advocate for their principles. This study aims to uncover Yusuf al-Qaradhawi's thoughts on the methodology of understanding Hadith in his book